Daycare Recommendation System Using Fuzzy Logic Method and Haversine Formula (Case Study : Medan City) - Br Sirait, Friska Pegrisentia; Hayatunnufus, Hayatunnufus; Hardi, Sri Melvani (Talenta Publisher, 2024)
The problem currently faced is the lack of trust from some parents towards daycare due to the lack of detailed information about daycare and the lack of attractive promotional media for working parents to entrust their children. Therefore, a decision support system is needed that uses the fuzzy logic method and haversine formula to assist in decision making when choosing the best alternative in daycare selection. The criteria used in this study were price, distance, quantity of caregivers, quality of caregivers, and facilities and infrastructure. The results of this study indicate that the system calculations are in accordance with manual calculations and the results of system testing prove that this system percieved of usefulness it has an actual score of 93.69% (0.9369), in terms of percieved ease of use it has an actual score of 93.21% (0, 9321), in terms of attitude toward using it has an actual score of 92.68% (0.9368) and in terms of behavior in use it has an actual score of 91.19% (0.9119). This was obtained by distributing questionnaires to 28 users (parents) during system testing.